2004
DOI: 10.1113/jphysiol.2003.056911
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress alters cardiovascular responses in adult rats

Abstract: Environmental factors in early life are clearly established risk factors for cardiovascular disease in later life. Most studies have focused on nutritional programming and analysed basal cardiovascular parameters rather than responses. In the present study we have investigated whether prenatal stress has long-term effects on cardiovascular responses in adult offspring. Female pregnant Sprague-Dawley rats were subjected to stress three times daily from day 15 to day 21 of gestation. Litters from stressed and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
74
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 71 publications
10
74
2
6
Order By: Relevance
“…Animal studies show varying effects of PNMS on body weight, some suggesting decreased weight in adolescent and adult offspring (13), others increased (14,15), and some with no significant effects (16). These studies also suggest that PNMS exposure is associated with later hypertension (14) and features of insulin resistance (16).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Animal studies show varying effects of PNMS on body weight, some suggesting decreased weight in adolescent and adult offspring (13), others increased (14,15), and some with no significant effects (16). These studies also suggest that PNMS exposure is associated with later hypertension (14) and features of insulin resistance (16).…”
mentioning
confidence: 82%
“…These studies also suggest that PNMS exposure is associated with later hypertension (14) and features of insulin resistance (16). However, the impact of PNMS on cardiometabolic outcomes among humans is not entirely clear.…”
mentioning
confidence: 96%
“…Cardiovascular reactivity has several detrimental consequences for human health: high BP reactivity has been linked to hypertension, 12 increased left ventricular mass, 13 carotid atherosclerosis 14 and all-cause mortality. 15 Data from experimental rat models have shown that prenatal malnutrition 16 and prenatal stress, 17 potential determinants of smaller body size at birth and shorter length of gestation, are associated with exaggerated cardiovascular reactivity to restraint stress. In humans, we are aware of only two studies that have examined whether BP reactivity in adult life is predicted by body size or gestational age at birth.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, prenatal stress is associated with negative pregnancy outcomes such as low birth weight, reduced litter sizes and lower survival rates (de Catanzaro 1988, Pratt & Lisk 1991, Brunton & Russell 2010, and in the adult offspring, it is associated with heightened anxiety (Fride & Weinstock 1988, Vallee et al 1997, Fan et al 2009, Brunton & Russell 2010, enhanced or prolonged hypothalamo-pituitary-adrenal (HPA) axis (Fig. 1) responses to acute stress (Takahashi & Kalin 1991, Weinstock et al 1992, McCormick et al 1995, Koenig et al 2005, Fan et al 2009, Brunton & Russell 2010, hypertension (Igosheva et al 2004), impaired glucose homoeostasis (Brunton et al 2013), insulin resistance (Nilsson et al 2001), diet-induced obesity (Nilsson et al 2001, Tamashiro et al 2009), impaired neural development (Lemaire et al 2000), cognitive deficits (Lemaire et al 2000, and abnormal social (Patin et al 2005, Lee et al 2007 and reproductive behaviours (Holson et al 1995, Frye & Orecki 2002.…”
Section: Introductionmentioning
confidence: 99%